PERAN SERTA NOTARIS DALAM PELAPORAN TRANSAKSI KEUANGAN MENCURIGAKAN PENDANAAN TINDAK PIDANA TERORISME DI ERA 4.0 DAN 5.0 - Rosi Maryana; Endang Purwaningsih; Irwan Santosa (LPPM Universitas Bina Bangsa, 2023)
The government currently involves the notary profession in the obligation to report suspicious financial transactions, especially for funds used for terrorist activities in the country through several regulations issued. This research is based on finding out how the implementation of Notary Participation is related to the obligation to report suspicious financial transactions on Terrorism Financing in the 4.0 and 5.0 eras as well as the supporting factors and legal obstacles. This research uses a normative juridical investigation with a futuristic approach/concept of draft laws that will apply in the future or towards the future symbol of dynamic and change and the results of extracting data and information are studied qualitatively supported by interviews with several sources in the field. Notaries who are required to report suspicious financial transactions are strongly advised to apply the Principles of Recognizing Service Users and submit Suspicious Financial Transaction Reports through the GoAML application to PPATK when acting on behalf of the parties/appearers. The supporting factor for this reporting is legal protection for the Notary himself and the Notary in submitting the suspicious transaction is constrained by keeping the secret of the position regulated in the Notary Office Act. Administrative sanctions, civil sanctions and criminal sanctions will always overshadow the notary in his activities in carrying out this reporting obligation